Intravitreal ranibizumab for diabetic macular oedema in previously vitrectomized eyes. Issue 1 (30th July 2016) - Laugesen, Caroline Schmidt; Ostri, Christoffer; Brynskov, Troels; Lund‐Andersen, Henrik; Larsen, Michael; Vorum, Henrik; Sørensen, Torben L.
Abstract: Purpose: There is little information about the efficacy of intravitreal vascular endothelial growth factor (VEGF) inhibition in vitrectomized eyes. This study aimed to evaluate the efficacy of anti‐VEGF (ranibizumab) on diabetic macular oedema in previously vitrectomized eyes. Methods: A nationwide retrospective review of medical records from 2010 to 2013. Results: We identified 33 previously vitrectomized eyes in 28 patients treated with ranibizumab injections for diabetic macular oedema. Median follow‐up was 323 days (interquartile range 72–1404 days). Baseline mean visual acuity was 0.57 logMAR (95% CI 0.13–1.01) before injections. After an average of 4.7 injections (range 1–15), mean visual acuity remained stable at 0.54 logMAR (95% CI 0.13–0.95) with a mean improvement of 0.03 (p = 0. 45, 95% CI −0.12 to 0.06). In 12 eyes (36%), visual acuity improved 0.1 logMAR or more, in 12 eyes (36%), vision was unchanged (gain or loss of 0–0.05 logMAR), and in nine eyes (27%), vision decreased 0.1 logMAR or more. Mean central foveal thickness (CFT) on optical coherence tomography (OCT) scan was 412 μ m (95% CI 390–434 μ m) before injections. After injections, the mean CFT decreased to 352 μ m (95% CI 334–370 μ m). The mean reduction in CFT was 14% (95% CI 4–24%, p = 0.01). Sixteen eyes (48.5%) became devoid of oedema on the last OCT scan. Despite the significant reduction in CFT, the visual acuity remained unchanged. Conclusion: Intravitreal ranibizumab can be effective in previously vitrectomized eyes with diabetic macular oedema. However, the response is variable and should be carefully monitored.